1997
DOI: 10.1177/096120339700600611
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune aberration in sudden sensorineural hearing loss: association with anti-cardiolipin antibodies

Abstract: In view of the presence of autoantibodies against inner ear antigens, the pathogenesis of sudden deafness (SD) and progressive sensorineural hearing loss (PSNHL) is suggested to be of an autoimmune nature. However, microthrombosis of the inner ear may result from pathogenic anti-cardiolipin antibody (aCL) activity. We studied 30 patients (17 females and 13 males, age range 20-52 y), of whom 11 suffered from SD and 19 from PSNHL. All were clinically and serologically evaluated for association with autoimmune di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…[2][3] It is typically unilateral, 4 and may be partial or complete, and sudden or rapidly progressive. 1 Causes of SSHL may be infectious (viral or bacterial), vascular, immunomediated (within the inner ear or systemically), or resulting from neurological disease (migraine, multiple sclerosis), neoplasms or ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3] It is typically unilateral, 4 and may be partial or complete, and sudden or rapidly progressive. 1 Causes of SSHL may be infectious (viral or bacterial), vascular, immunomediated (within the inner ear or systemically), or resulting from neurological disease (migraine, multiple sclerosis), neoplasms or ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997 we reported our results on the presence of aCL in the sera of patients with SNHL [43]. Low to moderate positive aCL to one or both IgG/IgM isotypes were found in 8/30 (27%) patients, whereas none were detected in the healthy controls.…”
Section: Snhl and The Antiphospholipid Syndrome (Aps)mentioning
confidence: 92%
“…Less frequently described manifestations of APS include chorea [4,[64][65][66], transverse myelopathy [5,67,68], Guillain-Barre syndrome [6], sensorineural hearing loss [69,70] and ocular syndromes with retinal and choroidal ischaemia [71][72][73][74].…”
Section: Other Psychiatric Disordersmentioning
confidence: 99%
“…A large series of 30 patients [69] showed that 27% of patients with sensorineural hearing loss had low-to-moderate titers of aCL, as opposed to none from the control group. Naarendorp et al [70] described 6 patients who developed sudden sensorineural hearing loss and had elevated serum levels of aCL or LA.…”
Section: Sensorineural Hearing Lossmentioning
confidence: 99%